Work-life policies - National Symposium on Family Issuses 2007 : Pennsylvania State University); Crouter, Ann C.; Booth, Alan, 1935-2015. (Washington, D.C. : Urban Institute Press, 2009)
"Sociological essays on policies that could help employees balance their workplace responsibilities with their other responsibilities. Policies examined encompass organizational policies, municipal policies, state policies, and federal policies. Workers studied include salaried professionals and low-wage part-time hourly workers"--Provided by publisher.
Papers presented at the 15th Annual National Symposium on Family Issues held at Penn State University in October 2007.
Includes bibliographical references and index.
Keywords: Work and family -- United States -- Congresses; Corporate culture -- United States -- Congresses; Flextime -- United States -- Congresses; Hourly